2010
DOI: 10.1111/j.1468-8123.2010.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential for abiotic organic synthesis and biosynthesis at seafloor hydrothermal systems

Abstract: Calculations are presented of the extent to which chemical disequilibria are generated when submarine hydrothermal fluids mix with sea water. These calculations involve quantifying the chemical affinity for individual reactions by comparing equilibrium compositions with the compositions of mixtures in which oxidation-reduction reactions are inhibited. The oxidation-reduction reactions that depart from equilibrium in these systems provide energy for chemotrophic microbial metabolism. Methanogenesis is an exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 182 publications
(344 reference statements)
2
60
1
Order By: Relevance
“…Organic compounds in hydrothermal fluids may come from marine dissolved organic matter (DOM) recycling [12,13], subsurface biomass degradation [26], entrainment of organic detritus from local recharge zones, and subsequent degradation, or abiotic formation in the deep subsurface [27][28][29][30]. The latter is supported by many theoretical [31][32][33] and experimental work summarised in two reviews [34,35]. Conversely, some other studies reported the absence of organic compounds in hydrothermal fluids except at the Lost City alkaline vent field which is theoretically more favourable for abiotic synthesis [36].…”
Section: Geofluidsmentioning
confidence: 68%
See 4 more Smart Citations
“…Organic compounds in hydrothermal fluids may come from marine dissolved organic matter (DOM) recycling [12,13], subsurface biomass degradation [26], entrainment of organic detritus from local recharge zones, and subsequent degradation, or abiotic formation in the deep subsurface [27][28][29][30]. The latter is supported by many theoretical [31][32][33] and experimental work summarised in two reviews [34,35]. Conversely, some other studies reported the absence of organic compounds in hydrothermal fluids except at the Lost City alkaline vent field which is theoretically more favourable for abiotic synthesis [36].…”
Section: Geofluidsmentioning
confidence: 68%
“…The isotopic composition of CH 4 in the Fatu Kapa fluids falls into the abiotic gas category but differs from the typical isotopic signature of CH 4 at Mid-Atlantic Ridge's vent fields. and H 2 [31], nonane [78], or undecane [79]. As a difference the presence of C 16 and C 18 n-FAs in significant amount in the fluids from Fatu Kapa may represent a direct microbial contribution.…”
Section: Surface Manifestations Boreholes Inclusionsmentioning
confidence: 99%
See 3 more Smart Citations